DIVERSIFIKASI PANGAN: KEPOMPONG ULAT JATI (Hyblaea Puera) SEBAGAI PERMEN BERPROTEIN TINGGI - Setyawan, Alina Puspa Nurmalia; Iswoyo, Aulia Zahra; Ramadhani, Rima Octaviana; Prahersiwi, Langit Elora (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
HI-PROGUM is an animal candy that is rich in protein and good for the body. This research uses animal ingredients sourced from teak caterpillar cocoons (Hyblaea puera). This research aims to find out how to utilize teak caterpillar cocoons (Hyblea puera) as the latest effort to diversify food in Indonesia, to contribute to the development of nutritious, accessible, and affordable food products with a focus on providing protein sources that can improve nutritional quality and support the growth of children and to assess the feasibility of strengths, weaknesses, opportunities, and threats in the development of HI-PROGUM products as an alternative food innovation. The research method is carried out by experimentation through preparation, candy making process, and product production process. In the preparation process there is cleaning and sterilization of teak caterpillar cocoons. The process of making candy is done by mixing the ingredients of gelatin, sugar, and citric acid. The stages of making the product are cooling in the refrigerator, and testing the results both sensorially and chemically. Testing of protein content in candy was carried out at BPSMB Surakarta Laboratory. The results of the research obtained showed that the HI-PROGUM formula contained 12.7% protein. This shows that HI-PROGUM is proven to have higher protein levels than other gummy candies which only contain 8% protein. Sensory analysis was also carried out to determine the acceptance of gummy candy to consumers in terms of taste, texture, and color. The results obtained that HI-PROGUM contains high protein, so it can fulfill animal protein intake per day. It can also be an alternative to candy substitutes that are often consumed by children.